Place to stand - Berstrom, Kirk.; Stewart, Patrick, 1940-; Thomas, Kit.; Films for the Humanities (Firm); United Nations (Princeton, NJ : Films for the Humanities & Sciences, 1995)
Provides a brief overview of the history of the United Nations and its achievements in the areas of peacekeeping, global security, human rights, assistance to refugees, sustainable development, and more.
Editor, Joanne Feinberg ... [et al.] ; narrator, Patrick Stewart ; music, Benjamin Dowling.
General.
Keywords: United Nations -- History; Security, International